Telaah Buku teks Bahasa Arab Madrasah Aliyah (Studi Analisis Buku Ajar kelas 12 KMA 183 Tahun 2019) - Alfarizi Farhan Mokoagow; Muhammad Nur Iman; Mukhtar I Miolo (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2021)
This article discusses the study of Arabic textbooks that focus more on the material of maharah istima' based on aspects of KMA 183 Year 2019 consisting of KI 1 (Spiritual), KI 2 (Social), KI 3 (Knowledge), and KI 4 (Skills) which are then explained from each chapter of the material maharah istima'. This article uses library research method or literature review, namely data collected through reference journals, books, thesis, and others. This study aims to find out the results of competencies based on KMA 183 year 2019 which is focused on the material of the maharah istima' of all chapters. The result of the study in this article is that there is a shutter of knowledge or KI in all materials maharah istima' and when viewed from the level of conformity, all of these materials are in accordance with the curriculum KMA 183 year 2019.